The effect of resistance training Super Set in developing some special performance requirements for young handball players - Hussein, L.Dr. Omar Ali; Al-Ghurairi, Asst. Prof. Dr. Alaa Ibrahim Jassim; Al-Atabi, L. Dr. Tahseen Shaghi Abdul Hamoud (Sulaimani Journal for Humanities, 2026)
Handball is considered a global sport that has witnessed a remarkable development in recent years in all aspects, especially physical and skill. The modern play of various international teams and teams has been characterized by speed and strength in skill performance, which confirms the interest of international coaches in preparing players during the training stages of age groups The various physical, skill and psychological aspects of producing high-class players, the importance of research has emerged in the study of one of the modern scientific qualitative methods and the development of a set of exercises using the Super Set method and its effect on some physical and skill performance requirements. Training within the same muscle group during the training dose, which makes its scientifically thoughtful application an increase in the possibility of developing the performance abilities in the game of handball. As for the problem, it was represented by the traditional approach to training methods used in training players, especially the youth, which the researcher considered a research problem that can be highlighted by trying to keep pace with the development in preparing handball players according to modern scientific and objective programs and concepts. The study aimed to identify the effect of Super Set exercises on some of the physical and skill performance requirements of young handball players, and the temporal domain was from 7/7/2024 until 1/10/2024 and the human field represented the youth players of Diyala Handball Club in age (16-18) for the season Sports 2023-2024 As for the spatial domain, it is the hall of the Directorate of Youth and Sports / Diyala Sports Hall.
Keywords: Superset training; performance requirements